ANALYSIS OF KNOWLEDGE SHARING USING CANONICAL CORRELATION TOWARD ORGANIZATIONAL INNOVATION - Supartini , Vebi Dewi; Sukmawati, Anggraini; Anggraeni , Elisa (Jurnal Organisasi dan Manajemen, 2019)
This paper is based on the importance of knowledge sharing to create innovation in an organization to overcome the problem of PTPN competition with the private sector. The purpose of this study is to determine the relationship between knowledge sharing variables, which are tacit knowledge sharing and explicit knowledge sharing, on innovation variables, which are speed innovation and quality innovation. The data collection method used a questionnaire with a sample of 100 employees and data were analyzed using canonical correlation analysis. The results of the study showed that there was an influence on each variable. Explicit knowledge sharing had influence on the speed and quality of innovation and explicit knowledge sharing had influence on the speed and quality of innovation. Conclusions from this study were that both variables had a strong relationship, so companies can consider these variables in strategic planning.